Avaliação das condições operacionais de espectrômetro de emissão óptica com plasma acoplado indutivamente com configuração axial - Trevizan, Lilian Cristina (2007)
The goal of this thesis was the critical evaluation of the analytical capability of an inductively coupled plasma spectrometer (ICP OES) with axially viewed configuration. The general view that axially systems are mainly applied to samples with low matrix complexity was evaluated and the performance of this configuration was supposed to be similar to the one of radially viewed systems. Figures of merit such as stability, robustness, detection limits, linear dynamic range, precision and accuracy were monitored in function of equipment operating conditions, sample introduction system and the complexity of the sample matrix. Magnesium II / Mg I ratio showed to be an adequate parameter for evaluation of ICP OES operating conditions. Factorial design allowed the determination of robust conditions for different sample introduction systems and evidenced the inefficiency of the V-groove nebulizer when operated at low nebulization gas flow-rate. For this nebulizer, in contrast with the literature, robust conditions were attained at both high applied power and high nebulization gas flow-rate. Using robust conditions, lower detection limits were found and high accuracy was obtained for the analysis of complex samples of non-fat milk powder diluted in tertiary amines medium and austenitic steel decomposed with aqua regia. For alcoholic beverage analysis, it was necessary the use of similar alcoholic concentration for the reference solutions and samples in order to compensate transport effects due to the presence of organic compounds. However, deviations greater than 10 % were observed for some elements in wine analysis. The use of the standard additions method or matrix matching by Fe addition was not necessary for austenitic steel analysis and calibration was performed with reference solutions in aqua regia 1.2 % v v-1 medium. Severe matrix effects in axially viewed ICP OES configuration did not occur and this configuration was competitive with radially viewed systems. An additional advantage of axially systems is the lower detection limits. However, the use of robust conditions caused a small decrease in linear dynamic range and can decrease the life-time of radio-frequency source and quartz torch of the equipment. Finally, the instrument software for semiquantitative analysis was evaluated and its performance was suitable for implementation of a screening procedure for biological samples microwave-assisted acid decomposed. This method allowed quantitative results for the majority of elements evaluated.